Comparative Analysis: The Effect of Macro and Micro Environment on Marketing Strategy and Marketing Performance of Small Medium Enterprises (Survey on Group of Small Medium Enterprises of Food and Non-Food Products in Cianjur Regency, West Java, Indonesia - Maqin, R. Abdul; Hendri, Nevi (International Review of Management and Marketing, 2017)
This study was a comparative analysis about marketing strategy and performance of groups of food and non-food small-micro industries in Cianjur regency, West Java. The problem in this study was to know the effect of macro and micro environment on the formulation of marketing strategy to improve marketing performance. The result showed that the formulation of marketing strategy could be achieved through the consideration of macro and micro environment. It could also improve the marketing performance of food and non-food small medium enterprises (SMEs). There were both different strategy and performance in marketing and performing the food and non-food SMEs. Keywords: Macro and Micro Marketing Environment, Marketing Strategy Formulation, Marketing Performance JEL Classification: M31